Sistem Informasi Assesmen Lembaga Sertifikasi Profesi (LSP) Energi Mandiri Jakarta - Iwan Mulyana; Enden Sulastri Puri (LPPM STMIK AL MUSLIM, 2022)
The problems that arise in the process of professional certification bodies are the document system has not been arranged neatly and does not yet have an information system for professional certification bodies (LSP) and do not have a direct link system that can be seen by potential participants so that the results of the announcement of participants and the graduation of the certification body have not been maximized in serving the participants who take part in this professional certification. With the Energy Mandiri Professional Certification Agency Assessment Information System (LSP), it can improve the quality, especially in services to prospective participants and participants as well as in tidying up related documents related to professional certification. Unified Modelling Language (UML) which consists of a use case diagram, activity diagram, sequence diagram and class diagram. Thus, it can be ascertained that the Energy Mandiri Professional Certification Institute (LSP) Assessment Information System can provide administrative convenience and can provide services to its participants at the Energi Mandiri Professional Certification Institute (LSP).